Corrosion inhibition of Polyalthia longifolia leaves extract in 1m HCl solution on mild steel - Zubairu, Abdu; Gimba, Abdullahi S. B.; Waziri, Abubakar B. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2021)
Corrosion is a very common phenomena in the manufacturing as well as chemical process industries. Corrosion has generated wide amount of interest worldwide because of its potential hazards to process equipment and machineries; which often leads to associated downtimes as well as adverse economic and safety consequences. The use of inhibitors is one of the most practical and efficient technique of protection against corrosion. In this work, the corrosion inhibition efficiency of polyalthia longifolia leaves extract in 1M HCl solution on mild steel surface was investigated using the standard gravimetric (weight loss) method. The results indicate that the extract could serve as a good green inhibitor. The inhibition efficiency increases with increase in the inhibitor concentrations. For the mild steel samples investigated in this work, about 70% inhibition efficiency was achieved with only 1.0 ml extract solution per 40 ml of 1.0 M HCl solution after five (5) days; and under same conditions, increasing the amount of extract by fivefold yielded only 10% increase in the inhibition efficiency for the same test period. The inhibition efficiency was also found to significantly increase with time of exposure for the first 48 hours of the experiment, but the increase was rather gradual at later times for all levels of extract concentrations